(untitled) (Bangladesh Journal of Pharmacology, 2015)
The chloroform and methanol extracts of Opuntia monacantha were studied for its hepatoprotective effect against paracetamol induced liver damage in rabbits. Results proved that both extracts at 200, 400 and 600 mg/kg body weight in one week protocol showed significant (p<0.001) hepatoprotective activity by reducing the magnitude of liver markers including alanine aminotransferase, aspartate aminotransferase, alkaline phasphatase and total bilirubin levels. The results were supported by histopathological studies of liver tissue. Chemical analysis of O. monacantha indicated the presence of alkaloids, tannins, saponins, flavonoids and polysaccharides and its hepato-protective potential may be due to the presence of flavonoids. Its is concluded that 600 mg/kg is the potent dose of both extracts of O. monacantha as hepatoprotective plant.